Роль міжнародних інноваційних кластерів у підвищенні економічної стійкості суб'єктів господарювання - Устименко, М. (Київський національний університет імені Тараса Шевченка, 2014)
У статті розкривається як інтеграція до міжнародних інноваційних кластерів впливає на підвищення економічної стійкості підприємств-учасників кластеру, регіонів і країн їх діяльності в умовах глобальної нестабільності, аналізуються можливі загрози і джерела нестабільності від залучення підприємств до таких міжнародних структур.

The influence of enterprises integration into international innovation clusters on the increasing of enterprises, countries and regions economic sustainability under the global instability are explored. Potential sources of instability and threats of the integration into international cluster structures are defined. Author outlines the main benefits of international innovation cluster for enhancement of economic agents sustainability, such as: possibility for joint exploitation of market opportunities and efforts consolidation for overcoming market threats, cluster self-sufficiency, effective cluster internal reorganization and adaptation in response to external changes. Three clusters (engineering for agriculture production cluster (Hersonska oblast and German enterprises), IT cluster (Lvivska oblast and Poland enterprises), cluster for R&D commercialization (Slobodzanschina euroregion)) are examined to uncover the role of international innovation cluster formation on enhancement of economic agents' economic sustainability.
The Role of International Innovation Clusters on Increasing Economic Agents Sustainability
Keywords: кластер; міжнародний інноваційний кластер; економічна стійкість; глобалізація; cluster; international innovation cluster; economic sustainability; globalization